Strategi Guru Pendidikan Agama Islam dalam Menanamkan Nilai-Nilai Multikultural pada Siswa SMA Negeri 1 Merauke, Papua Selatan - Irvan, Irvan; Amrulloh, Moch. Bachrurrosyady (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study aims to describe and analyze the strategies employed by Islamic Religious Education (PAI) teachers in instilling multicultural values in students at SMA Negeri 1 Merauke, South Papua. The research method employed is a qualitative descriptive approach, utilizing data collection techniques that include observation, interviews, and documentation. The results of the study indicate that the strategies implemented by PAI teachers include inclusive learning, contextual approaches, role models, and strengthening tolerance values ​​through religious and social activities. These strategies play an important role in building an attitude of mutual respect, cooperation between students across cultures, and reducing the potential for conflict caused by differences in background. This study concludes that PAI teachers have a strategic role in shaping students' multicultural character through an integrative and humanistic approach in the learning process. These findings contribute to strengthening multicultural learning in multiethnic areas such as Papua and are relevant to efforts to strengthen character education in Indonesia.